Sistem Informasi Geografis Perumahan Menggunakan Metode Rational Unified Process - Septiana, Yosep; Agustin, Yoga Handoko; Jungjunan, Aditya Rahma (Institut Teknologi Garut, 2024)
Geographic Information Systems (GIS) have become an increasingly important tool in the dissemination of housing information in this modern era. People need this information to make it easier to find housing that suits their needs and financial capabilities. The Housing and Settlements Service (DISPERKIM) is a government agency that regulates housing in an area. In collecting data on housing locations built at DISPERKIM, Garut Regency, Microsoft Excel is used, but to see housing location points, they are still separated by using Google Maps. Apart from that, the existing information system does not yet have a maps feature that contains geospatial data or points of distribution of housing locations to make it easier for people to find housing information based on the areas on the maps. The aim of this research study is to create a geographic information system. housing at Disperkim to make it easier to collect data on the location of housing being built and provide information to the public. The method used in this research uses Rational Unified Process (RUP) with the structure of Inception, Elaboration, Construction and Transition, through information system design using Unified Modeling Language (UML) which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams . The impact of this research resulted in a housing geographic information system which is managed by Disperkim and housing agents as admins and can be accessed by the public as users. The sources used in this information system are housing data from Disperkim and the Sikumbang PUPR website. The hope is that with the presence of this information system, people can more easily and efficiently find information about available housing locations.